Real time color projection for 3d models - Melo, Bruno Ferraz de (2017)
In this work, we present a solution for interactive visualization of virtual objects composed of a 3D model and a set of calibrated photographies. Our approach selects, projects and blends the photos based on a few criteria in order to improve perception of details while maintaining an interactive performance. It works as a dynamic texture map generator, where for each new view position and direction the best combination of the photos is sought. The main advantage of our technique is that it tries to preserve the original photo information as best as possible. Furthermore, the proposed method were compared with a popular texture mapping technique. Our method produced less artifacts in general, and was able to handle better large and non uniform datasets.